Voluntary exercise partially reverses neonatal alcohol‐induced deficits in mPFC layer II/III dendritic morphology of male adolescent rats. Issue 8 (17th June 2015) - Hamilton, G.F.; Criss, K.J.; Klintsova, A.Y.
ABSTRACT Developmental alcohol exposure in humans can produce a wide range of deficits collectively referred to as fetal alcohol spectrum disorders (FASD). FASD‐related impairments in executive functioning later in life suggest long‐term damage to the prefrontal cortex (PFC). In rodent neonates, moderate to high levels of alcohol exposure decreased frontal lobe brain size and altered medial PFC pyramidal neuron dendritic morphology. Previous research in our lab demonstrated that neonatal alcohol exposure decreased basilar dendritic complexity but did not affect spine density in Layer II/III pyramidal neurons in 26‐ to 30‐day‐old rats. The current study adds to the literature by evaluating the effect of neonatal alcohol exposure on mPFC Layer II/III basilar dendritic morphology in adolescent male rats. Additionally, it examines the potential for voluntary exercise to mitigate alcohol‐induced deficits on mPFC dendritic complexity. An animal model of binge drinking during the third trimester of pregnancy was used. Rats were intubated with alcohol (alcohol‐exposed, AE; 5.25 g kg−1 day−1) on postnatal days (PD) 4‐9; two control groups were included (suckle control and sham‐intubated). Rats were anesthetized and perfused with heparinized saline solution on PD 42, and brains were processed for Golgi‐Cox staining. Developmental alcohol exposure decreased spine density and dendritic complexity of basilar dendrites of Layer II/III neurons in the medial PFC (mPFC) compared to dendrites of control animals. Voluntary exercise increased spine density and dendritic length in AE animals resulting in elimination of the differences between AE and SH rats. Thus, voluntary exercise during early adolescence selectively rescued alcohol‐induced morphological deficits in the mPFC. Synapse 69:405–415, 2015. © 2015 Wiley Periodicals, Inc.